Emission Level of PM2.5 and its Association With Chronic Respiratory Symptoms Among Workers in Cement Industry: A Case of Mugher Cement Industry, Central Ethiopia - Mahlet Mekasha; Alemayehu Haddis; Tamrat Shaweno; Seid Tiku Mereta (Hamadan University of Medical Sciences, 2018)
In Ethiopia, occupation-related respiratory symptoms are extensively increasing with the expansion of cement manufacturing industries. However, little information is available on the extent of emissions and its association with chronic respiratory diseases. This study assessed the emission level of PM2.5 and its association with chronic respiratory symptoms among workers in Mugher Cement Factory, in 2018. A cross sectional study was employed on a total of 309 cement factory workers. Air check sampler, model 224-54, was used to measure the concentration of PM2.5. Variables with P value < 0.2 during bivariate analysis were selected as candidate for multiple logistic regressions. Significance level was set at P value <0.05. A total of 309 workers participated in the study with an overall response rate of 97%. The mean age of the respondents was 32.02 years (±4.7 SD). Emission levels of all PM2.5 samples were above the allowed standard. Among the workers, 50.8% had chronic respiratory symptoms and factors associated were: working in raw material receiving unit (adjusted odds ratio [AOR]= 7.5, 95% CI, 2.9, 19.4), cement milling unit (AOR = 2.4, 95 % CI ,1.2, 4.8), packing unit (AOR= 2.2, 95% CI= 1.1, 4.3), workers' monthly income level below 3000 ETB (AOR; 5.8, 95% CI,1.9, 17.6), and workers' regular medical checkup (AOR = 2.4, 95 % CI, 1.0, 5.2). The concentration level of PM2.5 and prevalence of chronic respiratory symptoms were high in the study area. Use of personal protective devices and periodic monitoring of installed pollution control devices is highly recommended.